THE EFFECTIVENESS OF THE TGT LEARNING MODEL ON LEARNING OUTCOMES ON THE MATERIAL OF RATIONALIZING THE DENOMINATOR OF ROOT FORM - Nabila Nurhaliza Ali; Ratna Yestina; Agis Mulyani; Supratman Supratman (USN Kolaka, 2023)
Team Games Tournament (TGT) learning is well prepared with the proper procedures. It will be better than conventional methods, such as lectures that tend to be monotonous. This encourages researchers to conduct research withthe title